Biodiversity of ostracod communities (Crustacea, Ostracoda) in a tropical floodplain. Issue 3 (3rd July 2017) - Pereira, Letícia C.; Lansac-Tôha, Fábio A.; Martens, Koen; Higuti, Janet
Abstract: Neotropical floodplains harbour both floating and rooted plants and are associated with rich ostracod communities. After dry seasons, flooding causes recruitment in 2 ways: floods bring in allochthonous macrophytes with associated pleuston communities, and these rising water levels rehydrate plants and attached (ostracod) eggs that dried at the onset of the dry season. We analysed the ostracods communities in the Araguaia River floodplain (Brazil) during 2 hydrological periods (dry and rainy) and evaluated the species distribution in relation to abiotic and biotic factors. We compared the ostracod fauna of 6 lakes in the dry and rainy period and 17 lakes in the rainy period. We tested the hypothesis that the highest values of ostracod community attributes (richness, density, and evenness) occur in the rainy season owing to the influx of allochthonous individuals and the rehydration of the dried autochthonous macrophytes. We indeed observed the highest richness and diversity of ostracods in the rainy season; the homogenizing effect of the flood pulse at the onset of the rainy season caused a more homogeneous fauna (lower beta diversity) during that hydrological period. The distribution of species showed a significant effect of both abiotic factors (local) and hydrological period (regional).